The COVID-19 pandemic and mental health in pregnant women: A review article - Arzamani, Niloufar; Soraya, Shiva; Hadi, Fatemeh; Nooraeen, Sara; Saeidi, Mahdieh (Frontiers in Psychiatry, 2022)
A rapid spreading of the COVID-19 virus in recent years had a great impact on every single aspect of live and the world faced with unexpected and unpredictable crisis in both physical and mental condition. As with any crisis, vulnerable individuals like pregnant women were the concern of societies. Several physiological and psychological changes occur during pregnancy which put individuals in a risk of mental health problems. During the outbreak of the COVID-19, pregnant women have experienced more psychological stresses, fear, anxiety, and depression. The prenatal mental distresses and psychiatric disorders may cause poor compliance, reduce help-seeking behaviors, and neglect to take the follow up screening visits and risk of harm for mother and others. Addressing the mental health in pregnant women is crucial to prevent the consequences. The purpose of this narrative review was to investigate the available literature on the impact of the COVID-19 pandemic on mental health in pregnant women and provide some recommendations to improve mental health in them. It also shed some light on providing mental health services for women during pregnancy and can be used by health professionals and policymakers.